Menginterkoneksi Sains dan Agama dalam Pembelajaran IPA di Sekolah Dasar - Yuliana Susanti (ISLAMIKA, 2019)
The development of science is interwoven with ideology. Therefore, a fundamental problem that always arises: is Islam complementary with natural science in harmony, or is there an unresolved complication between the metaphysical system based on religion and the demands of reason with empirical research? For a thousand years philosophers and Islamic theologians have considered this problem, which constantly invites intense and disagreeable debate. The word science comes from the Latin "scientia" which means knowledge. According to Webster New Collegiate Dictionart, the definition of science is "knowledge acquired through learning and proof" or "knowledge that covers a general truth of the natural laws that occur. Whereas according to Ibn Kaldun in Miqowin, science is a history of science developed almost entirely based on reason and empirical world experience.